Representation and indexing of medical images - Moreno, Ramón Alfredo; de Sá Rebelo, Marina; Gutierrez, Marco Antônio (Anales de Documentación, 2011)
The interpretation of an image by the computer is a highly complex task. There is a huge gap between the human and computational understanding of images and its interpretation. In this paper we present some of the concepts involved in the representation, indexing and interpretation of computerized images, focusing on medical imaging. The representation of images by low-level features (such as color and texture) is described as well as the use of high-level features such as ontologies.